Linking of CuI Units by Tetrahedral Mo2E2 Complexes (E=P, As). Issue 64 (8th October 2020) - Schiller, Jana; Schreiner, Andrea; Seidl, Michael; Balázs, Gábor; Scheer, Manfred
Abstract: The reaction of [Cp2 Mo2 (CO)4 (μ, η 2:2 ‐E2 )] (A : E=P, B : E=As, Cp=C5 H5 ) with the WCA‐containing Cu I salts ([Cu(CH3 CN)4 ][AlOC(CF3 )3 4 ] (CuTEF, C ), [Cu(CH3 CN)4 ][BF4 ] (D ) and [Cu(CH3 CN)3.5 ][FAlOC6 F10 (C6 F5 )3 ] (CuFAl, E )) affords seven unprecedented coordination compounds. Depending on the E2 ligand complex, the counter anion of the copper salt and the stoichiometry, four dinuclear copper dimers and three trinuclear copper compounds are accessible. The latter complexes reveal first linear Cu3 arrays linked by E2 units (E=P, As) coordinated in an η 2:1:1 coordination mode. All compounds were characterized by X‐ray crystallography, NMR and IR spectroscopy, mass spectrometry and elemental analysis. To define the nature of the Cu⋅⋅⋅Cu⋅⋅⋅Cu interactions, DFT calculations were performed. Abstract : The systematic study of the reactions of tetrahedral Mo2 P2 and Mo2 As2 ligand complexes towards Cu I salts containing WCAs brings to light a surprising new coordination behavior. Linear Cu3 chains stabilized by polypnictogen ligand complexes in a novel η 2:1:1 ‐coordination mode were observed, which reveal short Cu–Cu distances. This stabilization is realized by both the σ‐coordination of the lone pairs of the pnictogen atoms and the π‐coordination of the σ bond of the E2 unit towards the Lewis acidic Cu I centers.